Nilai-nilai Pendidikan Karakter dalam Serat Pedhalangan Ringgit Purwa VII Episode “Pandu Papa” - Yeni Eria Ningsih; Suryo Ediyono (Universitas Negeri Malang, 2018)
Nowadays, Indonesian has lost the local wisdom that characterizes the nation's culture. Character building is important thing ways to overcome the moral degradation of people right now. The research method used in this research is content analysis method by using qualitative approach. The results showed five values of character building contained in Serat Pedhalangan Ringgit Purwo VII Episode